Обратная нестационарная задача теории упругости для цилиндрической оболочки - Янютин, Е. Г.; Шарапата, А. С. (НТУ "ХПИ", 2004)
Numerically analytical solution of the ill-posed inverse problem in identification of the changing in time regularity of non-stationary impulsive loading steady to errors which affects the round cylindrical shell of a finite length is given. Axisymmetric movement of a joint-supported shell in the limits of elasticity is modelled grounded on S.P.Timoshenko's specified theory.
Keywords: НДС тел; импульсное нагружение; упругая деформация; осесимметричное деформирование; идентификация нагрузок